INDICATIONS AND RESULTS OF A NEW L-SHAPED MACULAR BUCKLE TO SUPPORT A POSTERIOR STAPHYLOMA IN HIGH MYOPIA. Issue 12 (December 2015) - Parolini, Barbara; Frisina, Rino; Pinackatt, Sajish; Gasparotti, Roberto; Gatti, Enza; Baldi, Andrea; Penzani, Roberta; Lucente, Angela; Semeraro, Francesco
Abstract : Background: The efficacy of a macular buckle in treating myopic traction maculopathy was studied. Methods: Fifty eyes with myopic traction maculopathy, in the form of macular detachment with macular hole (MHMD), or without macular hole (MD) and macular foveoschisis (MF), were treated with vitrectomy combined with macular buckle or with a macular buckle without vitrectomy. Results: Combined group : The combined group comprised 10 eyes with MHMD, 6 eyes with MD, and 4 eyes with MF. The retina was attached in 100% of MD and MHMD and the MF was improved in 100% of cases. The hole was closed in 60% of MHMD. The mean initial and final Snellen best-corrected visual acuity was 20/500 and 20/100 for MHMD, 20/200 and 20/60 for MD, and 20/200 and 20/50 for MF. The mean surgical time was 80 ± 35 minutes. Fundus angiography or indocyanine green revealed no alteration of the chorioretinal blood flow. Buckle shortening was required in 6/20 (30% of cases) patients for lateral extrusion of the sponge through the conjunctiva with the first sponge model. This complication was overcome by changing the arm of the buckle. Buckle group : The buckle group comprised 5 eyes with MHMD, 11 with MD, and 14 with MF. The retina was attached in 100% of MHMD, MD, and MF. The macular hole was closed in 60%. The mean initial and final Snellen best-corrected visual acuity was 20/800 and 20/60 for MHMD, 20/125 and 20/50 for MD, and 20/200 and 20/63 for MF. The mean postoperative decrement in axial length was 1.21 mm. The mean surgical time was 35 ± 15 minutes. Fundus angiography or indocyanine green revealed no alteration of the chorioretinal blood flow. Complications included conjunctiva erosion (15%), diplopia (7.7%), and pain (3.8%). Magnetic resonance imaging showed flattening of the posterior staphyloma. Conclusion: Considering the possible complications and technical difficulties of vitrectomy, we suggest that the macular buckle alone should be the first treatment of myopic traction maculopathy. Vitrectomy should be reserved only for cases of tangential tractions. Abstract : Macular detachment with and without macular hole and foveoschisis are complications of a posterior staphyloma in highly myopic eyes. The study demonstrates the safety and efficacy of a macular buckle, which can be implanted either combined with vitrectomy or alone.